Avaliação comparativa na pós-graduação stricto sensu entre Brasil e Portugal: um estudo de caso na engenharia civil - Sartori, Tatiane (2013)
In Brazil the Graduate Programs are evaluated by the Coordination of Improvement of Higher Education Personnel who have autonomy to carry out the assessment in all graduate programs in the country. There, by universities, a major concern as the quality of graduate programs with Capes intensified, year after year, verification of the evaluation criteria and the search for increased quality in the graduate studies program. In Portugal, the postgraduate programs are evaluated by A3ES, who will the Agency for Assessment and Accreditation of Higher Education, which evaluates the education and the standards also seeking the quality of education in the country. Based on this, the question arose of research: A comparison of the evaluation criteria used in graduate programs in Brazil and Portugal may suggest best practice models used in order to improve the quality of graduate education in Brazil? In the solution of this question proved necessary to survey the theoretical and conceptual knowledge for the better by the author on the topic as well as a comparison between two educational institutions, and in Brazil evaluated the graduate program in engineering civil Federal University of Santa Maria (UFSM) and Portugal evaluated the same program at the Institute of Engineering of Porto (ISEP). Through benchmarking comparison was possible to verify that Brazil is more developed in the case of the experience that the Capes have in terms of ratings, but Portugal is constantly seeking growth through improvements in the quality of assessments by A3ES in educational institutions. For criteria, there were similarities and the results were positive for both institutions analyzed.